泛灰数学在机器人机构误差分析中的应用 - 罗佑新 (Jixie chuandong)
The universal grey mathematics was introduced and its software was developed. The universal grey method of robot mechanism error analysis was studied. At last, an example was given with PUMA560 type robot. The universal grey mathematics provides a new method for robot mechanism error analysis and it has a wide extended values.